Suicide attempts in Brazil, 1998–2014: an ecological study - Davi Félix Martins Junior; Ridalva Martins Felzemburgh; Acácia Batista Dias; André C. Caribé; S. Bezerra-Filho; Ângela Miranda-Scippa (BMC Public Health, 2016)
Abstract Background Attempted suicide is the main predictor of suicide constituting a major public health issue worldwide. It is estimated that for every completed suicide, 10 to 20 suicide attempts occur. Important part of the occurrences of suicide attempts in Brazil are registered in the hospital information system for coverage of more than 70 % allows to evaluate the extent of this problem in the country. The scope of this article is to analyse hospitalizations resulting from suicide attempts at public hospitals or services contracted out by the public health system (SUS) in Brazil from 1998 to 2014. Methods This is an ecological study of secondary morbidity data obtained from the Hospital Information System. The overall rate of suicide attempts per 100 000 (105) individuals and rates stratified by age group and sex were calculated. To measure trends, simple linear regression coefficients were calculated. The hospital mortality rate was calculated per 100 individuals. Results The overall rate of hospitalization decreased from 1998 to 2014. The young and adult age groups had the highest hospitalization rates. Men were admitted more and the elderly had higher hospital mortality rates. The main cause of hospitalization was poisoning, accounting for 70.4 % of hospitalizations. Among the people who used poisoning by non-medical drugs as the method of attempted suicide, 58 178 (69.6 %) were men and 49 585 people who are poisoned by medical drugs (60.1 %) were women. Conclusions Although hospitalization rates for attempted suicide have declined in Brazil, it remains a serious public health problem. Because a suicide attempt is the main predictor of suicide, studies to identify those most vulnerable to attempted suicide will help in the development of prevention strategies for mental health.